ANALISIS PERLINDUNGAN HUKUM PASIEN DALAM PRAKTIK TELEMEDICINE MELALUI APLIKASI HALODOC - Widyaningrum , Ratna (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
The advancement of information technology has driven the development of telemedicine services, such as Halodoc, which facilitate online medical consultations. While enhancing accessibility, this service faces legal challenges related to patient protection and doctor liability, including risks of inaccurate diagnosis, limited physical examinations, and potential violations of data privacy. This study aims to examine how legal protection is provided to patients in telemedicine practices on the Halodoc platform and how doctors' legal responsibilities apply if patients suffer harm. The research employs normative legal research methods, utilizing statutory, conceptual, and comparative approaches. It analyzes primary, secondary, and tertiary legal materials using deductive reasoning. The findings indicate that legal protection for patients in telemedicine is categorized into preventive and repressive measures. Preventive protection is implemented through informed consent and medical record documentation, while repressive protection involves sanctions and compensation claims against doctors who commit medical errors. Doctors’ legal responsibilities in telemedicine encompass civil liability, which includes compensation for breaches of contract (wanprestasi) or unlawful acts; criminal liability, which may result in a maximum imprisonment of one year or a fine of up to Rp50,000,000.00; and administrative liability, which may lead to the revocation of a Registration Certificate (STR) or a Practice License (SIP).